Geração de modelo de regressão linear múltipla, a partir dos dados do software medina, para prever o afundamento de trilha de roda em função de parâmetros do tráfego, da base e do subleito - ALMEIDA, Danilo Ferreira de (2023)
The design of flexible pavements is in the process of adaptation, the tendency is to gradually replace empirical methods with empirical-mechanistic methods, such as the MeDiNa method. However, the MeDiNa software requires complex tests for the complete characterization of the materials, which are not widely accessible, especially in the North region of Brazil. This induces the designer to search for correlations in the literature to obtain the MeDiNa input parameters, which adds uncertainties and produces errors in the dimensioning. Therefore, this work aims to generate a model for predicting Wheel Track Sink (ATR) as a function of traffic, base and subgrade parameters. For this purpose, four parameters of the base and subgrade were varied in five levels and the traffic in two levels, which resulted in 1250 simulation scenarios, which were introduced in MeDiNa for the calculation of ATR. With data from 1250 simulation scenarios, a multiple linear regression model was created to predict the results of ATR and these results were compared with those calculated by the MeDiNa software. The main results were: the ATR prediction model presented R² = 0.693, that is, approximately 70% of the results are explained by the model, a good result considering that only 5 variables were used to characterize the materials; The permanent deformation parameters Ψ4 and Ψ3 were the parameters that most modified, directly and inversely proportionally, respectively, the ATR results; The Poisson coefficient and the N number (traffic) were the parameters that least modified the ATR results. Finally, it is concluded that the objective was achieved and that the model is an important tool to assist the designer in making decisions about the design of floors using the MeDiNa software.